Prevalence of Typhoid Fever among Admitted Patients of Federal University of Lafia Teaching Hospital, Lafia, Nasarawa State: A Retrospective Observational Study (Lafia Journal of Scientific and Industrial Research, 2026)
Typhoid fever remains a significant public health challenge in Lafia, Nasarawa State, with young adults disproportionately affected. This study investigated the prevalence, morbidity, and mortality of typhoid fever among admitted patients at the Federal University of Lafia Teaching Hospital (FULAFIA TH) from 2021 to 2025. A total of 72 cases were documented, with the highest morbidity observed in the 21–30-year age group (25%) and pediatric population (0–10 years, 16.7%). Mortality was concentrated in adults aged 21–40 years, with a case fatality rate (CFR) peaking at 27.8% in the 21–30 age group. Annual trends revealed fluctuating CFRs, ranging from 0% to 18.8%, suggesting variable clinical outcomes possibly linked to delayed presentation and antimicrobial resistance. The study underscores the urgent need for targeted public health interventions, including improved water infrastructure, early diagnostics, and student health programs to mitigate the burden of typhoid fever in Lafia.
Keywords: Typhoid Fever; Prevalence; Morbidity; mortality